MALIGNANCIES DETERMINED BY UPPER GASTROINTESTINAL SYSTEM ENDOSCOPY IN 1400 CASES - Tülay SARIÇAM; Eser VARDARELİ and Ayşegül HARMANCI and Yekta KIŞIOĞLU and Nur KEBAPÇI and Esat ERENOĞLU (Turkish Journal of Gastroenterology, 2020)
-